The Challenges of Nation-Building and Peace-Building in Nigeria: Array - Igbini, Mevayerore Daniel (Journal of Danubian Studies and Research, 2020)
Nation-building can be seen as a process of constructing or structuring a national identity using the state power which aim at the unification of the people within the state so that it remains politically stable and viable in the long run. United States and Israel have consistently and persistently pursued the new nation building designed to integrate their people, Nigeria continues to grope up around the orbit of nation-building without a genuine attempt to rotate it. Against this backdrop, this paper examined the role(s) political scientists in the overall project of nation building in Nigeria. This paper relies on secondary data collected from books and journal articles, and was content analyzed in relation to the scope of the paper. The paper concludes that without an effective leadership provision, no nation-building is achievable and this is where the role of the political scientists is seriously needed.